RANCANGAN SISTEM INFORMASI PEMBAYARAN BERITA ADVERTORIAL PADA CV. FOKUS JAMBI - Elzas -; Irma Suana (JURNAL AKADEMIKA)
The article of Scientific work will explain step by step about design and build a Project System Information Payment Advertorial News on the CV. Fokus Jambi which aims to facilitate the performance of the company, especially a part of assistant editor in data processing of Payment Advertorial News to be more effective and efficient, and to be able used to decision making. This application is designed by use Visual Basic 6.0 and Database MySQL Server relating to the research conducted by field of study, literature and laboratory study. After this application is made, in order to be able implementation very well and there is development in the next time, so this application will be better. And can be operated optimally by the company to data processing of Payment Advertorial News.